A REVIEW ON FLASH CHROMATOGRAPHY AND ITS PHARMACEUTICAL APPLICATIONS - Sandesh, J. Srikanth Sandesh; Shyamala; Swapana, Kurva; Balaiah, Sirra; Sharma, J V C (Journal of Biomedical and Pharmaceutical Research, 2021)
Earlier column chromatography was used for preparative purposes as well as for reaction control in organic synthesis. Column chromatography is an extremely tedious stage in any laboratory and can quickly become a point of congestion for any process lab. Flash chromatography is a technique developed as a modification of preparative column chromatography. This is an air pressure driven technique comprising of medium and short column chromatography, optimised for rapid separation of organic compounds. Modern flash chromatographic system consists of pre- packed plastic cartridges where in the solvent is pumped through the cartridge. By employing high pressure gas, the efficiency and speed of classical column chromatography can be increased. Flash chromatography is an easy & quick approach that is economical to preparative liquid chromatography. The content mentioned in this article mainly focuses on the various components, general principles, procedures and applications of flash chromatography.